Acute Kidney Injury in Children With Acute Respiratory Failure. (October 2018) - Villacrés, Sindy M.; Medar, Shivanand S.; Aydin, Scott I.
Background . Acute kidney injury (AKI) is common in critically ill children and develops in association with organ system dysfunction, with acute respiratory failure (ARF) one of the most common. We aim to study AKI in the pediatric ARF population. Methods . Data were retrospectively collected on children aged 1 day to 18 years admitted to the pediatric intensive care unit (PICU) with ARF between 2010 and 2013. Descriptive statistics and multivariate analyses utilizing Mann-Whitney U, Wilcoxon signed rank, χ 2, or Fisher's exact tests were performed to identify risk factors associated with AKI. Results . A total of 186 patients, with median age of 36 months (interquartile range 4-120 months) met the inclusion criteria. ARF was related to pulmonary disease in 49%. AKI was noted in 53% of patients. Patients with AKI had significantly higher serum creatinine ( P < .001) and lower estimated creatinine clearance ( P < .001) compared with those without AKI. Among patients with moderate and severe acute respiratory distress syndrome (ARDS), 64% had AKI versus 46% with mild or no ARDS ( P = .02). Patients with AKI had significantly lower PaO2 /FiO2 ratio ( P = .03), longer PICU ( P = .03), and longer hospital length of stay ( P = .01). ARDS patients were less likely to be AKI free on day 7 of hospitalization, as compared with those without ARDS. Multivariate analysis revealed positive end expiratory pressure (odds ratio [OR] = 1.2, confidence interval [CI] = 1.0-1.4; P = .03) and admission serum creatinine (OR = 27.9, CI = 5.2-148.5; P < .001) to be independently associated with AKI. Conclusions . AKI is common in children with ARF. In patients with ARF and AKI, AKI is associated with ARDS and longer PICU and hospital length of stay. Positive end expiratory pressure and serum creatinine are independently associated with AKI.